Rediscovery of Polygonatum tessellatum F. T. Wang & Tang in Manipur, north-eastern India - Dhatchanamoorthy, Narayanasamy; Ravikumar, Kaliamoorthy; Balachandran, Natesan (Biodiversity: Research and Conservation, 2023)
Polygonatum tessellatum F. T. Wang & Tang (Asparagaceae) was rediscovered in Manipur after a gap of 97 years. Description, image, and current population size are provided on the basis of recent botanical explorations.